2021
DOI: 10.1021/acs.oprd.1c00010
|View full text |Cite
|
Sign up to set email alerts
|

Process Development of Tacalcitol

Abstract: A highly convergent, gram-scale synthesis of vitamin D3 analogue tacalcitol 1 is disclosed, starting from L-valine and Inhoffen–Lythgoe diol. Key features of the synthesis include modified Julia olefination reaction of β-oxybenzothiazol-2-yl sulfone with C/D ring containing aldehyde to access decagrams of fully functionalized C/D ring synthon. The Horner–Wadsworth–Emmons (HWE) reaction between the C/D ring fragment and commercially available phosphonate completes the carbo-skeleton, which is elaborated into ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Also in this case, both the HWE and Wittig reaction failed to provide the key steroidal intermediate 32 (data not shown). Thus, 2-((2-(2-methyl-2Htetrazol-5-yl)ethyl)sulfonyl)benzo[d]thiazole (36) (Scheme 6B) was prepared 23 and reacted with the C22-aldehyde 17 to give olefin 32 in 24% yield (E/Z ratio: 7/3) (Scheme 7). Compound 32 was hydrogenated with Pd/C in THF and finally submitted to Jones oxidation leading the desired 24-(N-2-methyl-tetrazol-5-yl)-5α-chol-7-en-3-one (12) in 44% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Also in this case, both the HWE and Wittig reaction failed to provide the key steroidal intermediate 32 (data not shown). Thus, 2-((2-(2-methyl-2Htetrazol-5-yl)ethyl)sulfonyl)benzo[d]thiazole (36) (Scheme 6B) was prepared 23 and reacted with the C22-aldehyde 17 to give olefin 32 in 24% yield (E/Z ratio: 7/3) (Scheme 7). Compound 32 was hydrogenated with Pd/C in THF and finally submitted to Jones oxidation leading the desired 24-(N-2-methyl-tetrazol-5-yl)-5α-chol-7-en-3-one (12) in 44% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Shin et al . reported that the synthesis of Tacalcitol 225 was achieved via Julia‐Kocienski olefination [66] . The intermediate product 228 was reacted with β‐oxybenzothiazol‐2‐yl sulfone 227 under Julia‐Kocienski reaction conditions and gave the desired E ‐olefine 224 a in 87 % yield.…”
Section: Synthetic Methodologiesmentioning
confidence: 99%
“…Shin et al reported that the synthesis of Tacalcitol225 was achieved via Julia-Kocienski olefination. [66] The intermediate product 228 was reacted with β-oxybenzothiazol-2-yl sulfone 227 under Julia-Kocienski reaction conditions and gave the desired E-olefine 224 a in 87 % yield. This resultant product was purified by flash chromatography and then was subjected toa sequence of chemical reactions such as HWE (Horner-Wadsworth-Emmons) reaction, deprotection and oxidation of hydroxyl groups, etc., to give the Tacalcitol 225.This compound was recrystallized by using MeOH/H 2 O solution to yield Tacalcitol monohydrate (Scheme 43).…”
Section: Synthesis Of Miscellaneous Compoundsmentioning
confidence: 99%